“We were like pilgrims from the 12th century. This is something! I do not praise, I appreciate it.” Camino de Santiago in The Memories of Polish peregrinos - Plichta, Paweł (Człowiek i Społeczeństwo, 2016)
This paper examines a few aspects of religiousness presented in various narratives offered by Polish authors of the Camino memoirs. The parameters that determine the individual dimensions of religiosity are self-confession, religious practices, religious knowledge, religious ideology, religious morals, religious experience, and religious community. This paper adopts an analytical approach to varied source material including literature and popular and scientific texts created by authors that walked the Camino de Santiago themselves.